Establishment and Characterization of Feline Mammary Tumor Patient-Derived Xenograft Model - Chuang, Hsiao-Li; Chang, Yi-Chih; Huang, Yi-Ting; Liao, Jiunn-Wang; Kao, Pei-Ling; Chen, Yi-Fei; Lin, Bin-Yin; Lin, Yi-Lo; Chen, Ter-Hsin; Wang, Yu-Chih (Animals (Basel), 2021)
Feline mammary tumor is a relatively commonly diagnosed neoplasm in the cat. Development of new veterinary cancer therapies is limited by the shortage of in vivo models that reproduce tumor microenvironment and metastatic progression. Four feline mammary tumor orthotopic patient-derived xenograft model (PDX) successfully established in NOD-SCID gamma (NSG) mice. The overall success rate of PDX establishment was 36% (4/11). Histological, immunohistochemical, and short tandem repeat analysis showed a remarkable similarity between patient’s tumor and xenograft. The tumor grafts conserve original tumor essential features, including distant metastasis. Primary FMT-1807 cell line isolated from FMT-1807PDX tumor tissue. Tumorigenicity of FMT-1807 cells expanded from PDX was assessed by orthotopic injection into NSG mice. Mice yielded tumors which preserve the lung and liver metastasis ability. This work provides a platform for FMT translational investigation.